2022
DOI: 10.1002/advs.202104576
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Enzymes in Plasmonic Silk Film for Synergistic Therapy of In Situ SERS Identified Bacteria

Abstract: Increasing antibiotic resistance becomes a serious threat to public health. Photothermal therapy (PTT) and antibacterial enzyme‐based therapy are promising nonresistant strategies for efficiently killing drug‐resistant bacteria. However, the poor thermostability of enzymes in PTT hinders their synergistic therapy. Herein, antibacterial glucose oxidase (GOx) is embedded in a Ag graphitic nanocapsule (Ag@G) arrayed silk film to fabricate a GOx‐synergistic PTT system (named silk‐GOx‐Ag@G, SGA). The SGA system can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…(E) AuNR@G-P-aspirin for enhanced NIRmediated PTT of solid tumor and simultaneously inhibit PTT-induced inflammatory response (Dong et al, 2018). (F) Thermostable Ag@G-GOx synergistic PTT platform for bacterial elimination (Liu et al, 2022). of protecting Ag NPs from oxidation, Song et al (2014) prepared a highly surface enhanced Raman scattering (SERS)-active AgCu graphitic nanocapsules (AgCu@G).…”
Section: Theranostics In Non-intrinsic Physiological Harsh Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(E) AuNR@G-P-aspirin for enhanced NIRmediated PTT of solid tumor and simultaneously inhibit PTT-induced inflammatory response (Dong et al, 2018). (F) Thermostable Ag@G-GOx synergistic PTT platform for bacterial elimination (Liu et al, 2022). of protecting Ag NPs from oxidation, Song et al (2014) prepared a highly surface enhanced Raman scattering (SERS)-active AgCu graphitic nanocapsules (AgCu@G).…”
Section: Theranostics In Non-intrinsic Physiological Harsh Conditionsmentioning
confidence: 99%
“…Based on the superior thermostability and photothermal property of AuNR@G, Xu et al (2019) reported a AuNR@G-doped hydrogel system for highly efficient photothermal antibacterial therapy for both Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus. Recently, Liu et al (2022) reported a GOx and Ag graphitic nanocapsules (Ag@G) co-loaded silk membrane theranostic system, the silk membrane enabled GOx to maintain good antibacterial activity during the photothermal antibacterial therapy process, the inert graphitic shell enabled Ag@G to keep excellent SERS performance and photothermal performance under high temperature and GOx-catalyzed production of large amounts of H 2 O 2 , SERS identification of bacteria in the bacteria-infected wound model and efficient synergistic treatment of bacteria were eventually achieved (Figure 1F).…”
Section: Frontiers Inmentioning
confidence: 99%
“…SERS applied for bacteria detection has great advantages, such as a fast detection speed and high sensitivity without using labeling agents such as antibodies, and, in particular, it has simultaneous detection capabilities for multiple types of bacteria [ 35 , 36 ]. In addition, SERS is considered a promising tool to detect bacteria in infected wounds or blood tissue without damaging the actual sample structure [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…doped the AgNPs onto the surface of a black phosphorus nanosheet to achieve a photocatalytic disinfectant to produce ROS and Ag species for bacterial killing . Recently, Liu et al reported a photothermal/enzymatic combined antibacterial treatment using the silk film decorated with graphite-encapsulated AgNPs and glucose oxidase . In silver therapy, the released silver ions (Ag + ) from the AgNPs is the main bactericide .…”
Section: Introductionmentioning
confidence: 99%